ANÁLISIS CRÍTICO DEL CONTENIDO DISCURSIVO: UNA APROXIMACIÓN HERMENÉUTICA AL CONCEPTO DE ACTIVOS INTANGIBLES DESDE DOS PERSPECTIVAS NORMATIVAS - JUAN PABLO HINCAPIÉ (Revista Criterio Libre, 2019)
The aim of this article of reflection is to unveil and analyze some conceptual particularities of intangible assets, using the qualitative research methodologies of content analysis, discourse and critical discourse analysis. Specifically, it seeks to know what can be critically observed in the accounting discourse on the treatment of intangible assets according to Regulatory Decree 2649 (1993) and International Accounting Standard 38 (2014), and, specifically, what is disclosed about the treatment of the intangible asset generated internally. The object of observation in this study is constituted by the regulatory characteristics that are available in intangible assets in these two regulatory frameworks. In the end, brief conclusions derived from the analysis are presented and an invitation to the potentialization and reflective deepening of the qualitative studies is extended, using qualitative research tools such as the Atlas T.I., among others